The Impact of Media and Islamophobic Practices in Shaping Muslim Identity in Contemporary American Literature: Case Study: Ayad Akhtar’s Disgraced (2012) - CHATTA,Souad; HAFFAF ,Aya Chaima; Hocine,Aicha (University of Ammar Theledji -Laghouat, 2021)
Islamophobia can be considered one of the world‟s contemporary major problems. In fact, its negative impact on Muslims‟ identity has reached an alarming point. The current paper aimed to analyze Muslims‟ situation in American society through the investigation of Ayad Akhtar's play, Disgraced (2012). In this research, the descriptive and analytical approaches were adopted to analyze the reasons and means that helped in the incensement of it. Therefore, our study suggested that the most serious damage resulting from Islamophobia lied in blurring Muslim‟s culture and Islamic identity. Essentially, the next decade is likely to witness a considerable rise in Islamophobia that will lead to a direct and violent clash between Muslims and non-Muslims